Efektivitas Restitusi dalam Perlindungan Korban Kekerasan Seksual di Indonesia: Analisis Yuridis dan Implementasi Praktis - Henny Yuningsih; Munawir Munawir (Dinasti Research, 2025)
This paper examines the effectiveness of restitution as a means of protecting victims of sexual violence in Indonesia, focusing on its legal analysis and practical implementation. Sexual violence is a serious issue that has negative impacts on victims, including physical and psychological trauma. Restitution, as a form of compensation provided to victims, is expected to assist in recovery and deliver justice. This study employs a qualitative approach, analyzing secondary data from various literature, legal regulations, and case studies. The findings reveal that although there are regulations supporting restitution, its implementation in the field faces various challenges, such as lack of public awareness, stigma against victims, and administrative barriers. Furthermore, the existing restitution mechanisms are not fully integrated into the criminal justice system, diminishing their effectiveness in providing protection. Therefore, it is crucial to strengthen the legal system and enhance collaboration among government agencies, civil society organizations, and other relevant stakeholders to optimize restitution as a tool for protecting victims. This research is expected to contribute to the development of policies and practices for protecting victims of sexual violence in Indonesia.